Effect of decision variables on yield and water productivity of onion under conventional furrow irrigation system in bako woreda, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2021)
Flow rate and furrow length are the main irrigation decision variables currently affecting yield and water productivity at farm level. Improper selection of these variables produces an over use of water and loss in crop production. The general objective was to investigate the effect of decision variables on yield and water productivity of onion under conventional furrow irrigation system, with specific objective to analyze the effect of flow rate, furrow length and their interaction on yield and water productivity of onion. The field experiment was laid out in randomized complete block design with factorial arrangement of three levels of flow rate (0.7, 0.98 and 1.3 L/S) and three levels of furrow length (25, 35 and 50 m) with three replications. Inflow out flow method was used to determine the infiltration characteristics of the soil and Irrigation depth was controlled by using 3-inch Parshall flume. The maximum non-erosive flow rate to the experimental site was fixed through design equation considering soil textural class and furrow bed slope. Effect of furrow length and flow rate on yield and water productivity of the onion were used for evaluation. Their analyses indicated that effect of furrow length and their interaction with flow rate on yield were not significant (p